Serum levels of platelet endothelial cell adhesion molecule-1 (PECAM-1) and soluble vascular endothelial growth factor receptor (sVEGFR)-1 and -2 in HIV associated preeclampsia - Semone Thakoordeen; Jagidesa Moodley; Thajasvarie Naicker (Taylor & Francis Group, 2017)
Objective: The angiogenic-antiangiogenic imbalance evident in preeclampsia (PE) may be used as a predictive tool to identify women likely to develop the clinical features in early pregnancy. Method: This retrospective study examined normotensive pregnant (n = 38) and preeclamptic (n = 38) HIV-infected and uninfected women to quantify sVEGFR-1 and -2 and PECAM-1 levels. Results: In contrast to PECAM-1, sVEGFR-1 and -2 differed according to pregnancy type (p = 0.07; p = 0.001; p = 0.002) but not by HIV status (p = 0.68; p = 0.13; p = 0.43). Conclusion: Irrespective of the HIV status, we report an upregulation of sVEGFR-1 with concomitant decline of PECAM-1 and sVEGFR-2 levels in PE compared to normotensive pregnancies.